CSR di Kampung Wisata Jambangan (Jurnal Ilmiah Pariwisata, 2014)
The characteristics of Surabaya tourism is urban tourism. With the limitations of natural attractions, Surabaya has an artificial tourism based on community based tourism in the residential area in Jambangan tourism village.TouristattractionsinJambanganusingexperientialtourism approach, which is touristsexperience firsthandandbe involved inlocal community life. Corporate social responsibility (CSR) in the field of urban tourism in Surabaya is done through three forms: the creation of tourist events, renovation or development of tourist attractions, and the creation of new tourist destinations or attractions. CSR in the tourist village Jambangan CSR categorized in terms of the development of tourist attractions. The background of implementation CSR in Jambangan because the location of business close from this village. CSR through assistance making catfish ponds, nursery fungi, and development of batik creations among the citizens of Jambangan. The goal is to have a diversity in Jambangan tourism village. This research uses descriptive qualitative method, in which the primary data source is obtained through interviews and observation, secondary data sources through the study of literature. Conclusions of this study are: ( 1 ) CSR in tourism will achieve the target and sustain if supported by community involvement, (2 ) The development of tourist destinations with CSR programs must adapt to the characteristics and local resources.